2021
DOI: 10.1088/1402-4896/ac3a4d
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic shift in magic nuclei within relativistic mean-field formalism

Abstract: The ground-state properties such as binding energy, root-mean-square radius, pairing energy, nucleons density distribution, symmetry energy, and single-particle energies are calculated for the isotopic chain of Ca, Sn, Pb, and Z = 120 nuclei. The recently developed G3 and IOPB-I forces along with the DD-ME1 and DD-ME2 sets are used in the analysis employing the relativistic mean-field approximation. To locate the magic numbers in the superheavy region and to explain the observed kink at neutron number N = 82 f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…2. Furthermore, from Brückner's prescription, no significant peak is found at N = 126 shell closure, corresponding to 208 Pb as also reported in earlier studies [8,11,12,36,37] and the references therein. This peak shifted to N=120 which is not a close shell for Pb nucleus.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…2. Furthermore, from Brückner's prescription, no significant peak is found at N = 126 shell closure, corresponding to 208 Pb as also reported in earlier studies [8,11,12,36,37] and the references therein. This peak shifted to N=120 which is not a close shell for Pb nucleus.…”
supporting
confidence: 83%
“…This is one of the most essential characteristics of nuclei that lies far from the stability line. Several recent studies have unequivocally demonstrated that the presence of kinks in symmetry energy of finite nuclei over the isotopic chain points to the existence of magic numbers [7][8][9][10][11][12]. The advancement in the sophisticated experimental radioactive ion beam facilities using the projectile-fragmentation reaction method with fast ion-beams at FRIB (USA) [13], RIKEN (Japan) [14], GSI (Germany) [15], FLNR (Russia) [16], CSR (China) [17] and SPIRAL2/GANIL (France) [18] have led to the renaissance of investigating the behaviour of symmetry energy at and above the saturation density [19].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the decay channels 231 Pu+ 4 He and 233 Pu+ 4 He displays a departure from the norm (highlighted in the footnote a), signifying the presence of a shell/sub-shell closure at N=139, 141 and Z=94 which corresponds to 231 Pu and 233 Pu, respectively. This is somewhat reminiscent of the appearance of peaks/kinks in symmetry energy of finite nuclei across the isotopic chain as indicators of shell/sub-shell closures [38][39][40].…”
Section: Resultsmentioning
confidence: 99%